Ancient perspectives on Paul - Nicklas, Tobias; Merkt, Andreas; Verheyden, Joseph (Novum testamentum et orbis antiquus / Studien zur Umwelt des Neuen Testaments, 2013)
While the so-called ”New perspective in Paul“ has been in the focus of New Testament exegesis for more than 25 years now, ancient interpretations of Pauline texts and ideas have been neglected widely. The present volume aims to fill this gap. Its articles concentrate on three different foci of modern exegesis: interpretations of Paul’s conversion, his ideas about the relation of “grace” and “works” and the fate of Israel. Several additional articles contrast these ancient perspectives with answers of modern exegesis.
Beitr. teilw. engl., teilw. dt
Keywords: Paulus -- Apostel, Heiliger; Bible -- Epistles of Paul -- Criticism, interpretation, etc; Bible -- Epistles of Paul -- Criticism, Textual; Bibel -- Paulinische Briefe; Israel -- Altertum; Konferenzschrift -- 2010 -- Regensburg; Urchristentum; Frühjudentum; Theologie; Bibel / Paulinische Briefe; Paulus <Apostel, Heiliger>; Geschichte Anfänge-430; Rezeption